Art and the creative unconscious : - Neumann, Erich (Princeton University Press, 1959)
Four essays on the psychological aspects of art. A study of Leonardo treats the work of art, and art itself, not as ends in themselves, but rather as instruments of the artist's inner situation. Two other essays discuss the relation of art to its epoch and specifically the relation of modern art to our own time. An essay on Chagall views this artist in the context of the problems explored in the other studies.